A Longitudinal Study of Human Antibody Responses to Plasmodium falciparum Rhoptry-Associated Protein 1 in a Region of Seasonal and Unstable Malaria Transmission - Fonjungo, Peter N. (American Society for Microbiology (ASM), 1999)
Rhoptry-associated protein 1 (RAP1) of Plasmodium falciparum is a nonpolymorphic merozoite antigen that is considered a potential candidate for a malaria vaccine against asexual blood stages. In this longitudinal study, recombinant RAP1 (rRAP1) proteins with antigenicity similar to that of P. falciparum-derived RAP1 were used to analyze antibody responses to RAP1 over a period of 4 years (1991 to 1995) of 53 individuals naturally exposed to P. falciparum malaria. In any 1 year during the study, between 23 and 39% of individuals who had malaria developed immunoglobulin G (IgG) antibodies detectable with at least one rRAP1 protein. However, the anti-RAP1 antibody responses were detected only during or shortly after clinical malarial infections. RAP1 antibody levels declined rapidly (within 1 to 2 months) following drug treatment of the infections. No anti-RAP1 antibodies were usually detected a few months after the end of malaria transmission, during the dry season, or by the start of the next malaria season. Thus, RAP1 IgG responses were very short-lived. The short duration of RAP1 antibody response may explain the apparent lack of response in a surprisingly high proportion of individuals after clinical malarial infections. For some individuals who experienced more than one malarial infection, a higher anti-RAP1 antibody response to subsequent infections than to earlier infections was observed. This suggested secondary responses to RAP1 and thus the development of immunological memory for RAP1.